Assessment of urban sanitation status and management gaps in a metropolitan city, Bangladesh: Potential challenges to achieve SDG 6 - Ferdous, Sazia; Chowdhury, Farah Noshin; Ali, Md. Liakath; Bodrud-Doza, Md.; Rahman, Md. Mostafizur (Frontiers in Water, 2022)
Concerns have been on the rise around the globe regarding better sanitation management, which is one of the basic human rights, owing especially to the present goal of sustainable development, more specifically Sustainable Development Goal (SDG) 6. Proper sanitation management is a challenging issue in Bangladesh. The purpose of this study was to investigate the current state of sanitation and hygiene facilities and management in Chattogram City, Bangladesh. This study was conducted via questionnaire survey, key informant information (KIIs), stakeholder meetings, and field visits. A survey was conducted on slum dwellers and non-slum dwellers (formal settlements) of the city. A total of 400(=n) randomly selected respondents were interviewed (200 from each group) from eight wards of the metropolitan city, six KIIs, and three stakeholder meetings. Field visits were made to observe the conditions along with a pilot survey to validate the questionnaires. A purposive sampling method was employed for this study, while both descriptive and quantitative statistical analyses were conducted. Statistical analysis of the survey results and field observation found inadequate sanitation and hygiene facilities, insufficient community toilets, improper waste disposal, and drainage facilities in the city. Sanitation was worse in slum areas than in the non-slum neighborhoods. 55.4% of slum dwellers had no/little awareness of the sanitary system. While 89% of families in slum areas use shared toilets, unhygienic toilets caused different diseases to 63.7% of respondents. Drainage conditions were almost equally insufficient in both groups. 65% of respondents did not have any community toilets in their locality. The sanitation management system is not well-equipped and it is a pressing need to make better plans and implement sufficient management strategy for the total sanitation of the city.